Decision making and the theory of the firm - Horowitz, Ira (Holt, Rinehart and Winston, 1970)
Professor Horowitz successfully blends concepts and techniques drawn from the neoclassical theory of the firm, statistical decision theory, mathematical programming, and econometrics. As a result he develops the traditional principles of microeconomics while simultaneously indicating how the neoclassical model can be altered to deal with issues raised by such a modification has for traditional precepts, and discussing the practical questions involved in the application of the theory for actual decision-makinbg purposes.